PERLINDUNGAN HUKUM DAN ETIKA BAGI PENGGUNA FINTECH PEER TO PEER LENDING DI INDONESIA - Rina Arum Prastyanti; Adnan Terry Suseno (Trunojoyo Madura University, 2021)
The rapid growth of illegal online loan services is also caused by the potential of the Indonesian people themselves to become a large enough market for online loan services. There are still many Indonesians who are not bankable, so many turn to illegal online loan services that are easier and faster. Currently, there are 105 illegal Fintechs that have been brought under control by the Investment Alert Task Force since 2018-2020. In terms of fintech dispute resolution, there is no dispute resolution agency that effectively resolves disputes. This is because the location of the parties is unclear, besides that the fintech lending administrator in the standard electronic contract clause does not specify a court. This research is a normative juridical research using the Systematic Literature Review Method which refers to Kitchenham (2019) with research stages using planning, implementation and reporting. The first stage begins with formulating the main objectives of this research. This is to identify what problems arise from the Peer to peer Lending industry. On November 13, 2020, OJK issued a draft regulation on P2P, which is planned to replace POJK 77, to provide legal certainty to the P2P business model and protect the public interest. Several provisions in the draft were adopted from OJK regulations that exist in other business sectors that are strictly regulated such as insurance, securities, and finance. The protection of peer to peer fintech lending business ethics has been stated in the AFPI 2020 special Code of Conduct Number 002/SK/COC/INT/V/2020. However, the rules of business ethics that have been made still have weaknesses which will have an impact on consumers' losses.